Rancang Bangun Sistem Informasi Desa Berbasis Website (Studi Kasus Desa Netpala) - Asmara jimi (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2019)
Abstract The development of the village government are now either in the presence of village funds from the central government that aim to advance, village the current rural development related to information technology support, almost luminance village need to improve information technology services to the.One example from the village, about the internet the internet is not currently only enjoyed by urban residents but comes to. village communityThe difficulty of access to information that is keen to develop research make village based information system website for the purpose of improving public services, village access to information can be obtained easily, for the villagers, promotion , potential of the village , population area and forth with, literature in a interview observation, field and drafting, system the website based information system able to improve services to the community so that information to the public can be accessed easily and accurately.